Kontestasi Kepentingan Pro-Growth Coalition dan Anti-Growth Coalition dalam Konflik Pembangunan Rempang Eco-City Tahun 2023 - Stephen Giovanni Walangare; Syaiful Bachri (Universitas Islam Darul Ulum Lamongan, 2023)
This research analyzing the conflict that occurred between the government and the residents of Rempang Island from the perspective of a growth machine in urban politics. PT MEG and Xinyi Group as investors together with representatives of the Central Government and BP Batam will be seen as a pro-growth coalition group in conflict with the residents of Rempang Island as an anti-growth coalition group. This research uses qualitative methods by analyzing secondary data in the form of literature studies and articles regarding the Rempang conflict from various mass media reports. This conflict was not handled well by the pro-growth coalition which did not carry out growth management and instead ignored the interests of the anti-growth coalition.